Keselamatan Diri dalam Qurban Idul Adha 1441 H sebagai Bentuk Pengabdian kepada Masyarakat Politeknik Penerbangan Palembang - Anton Abdullah; Wildan Nugraha; Fitri Masitoh; Sutiyo Sutiyo; Rinto Astutik (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2020)
The target and output of this activity are to implement the Tridharma of Higher Education, community service for lecturers in the Palembang Aviation Polytechnic environment, South Sumatra. The activity method used is 1) religious lectures, namely spiritual guidance to the Aviation Polytechnic extended family and local residents; 2) The lecture in which the resource person explained to the Aviation Polytechnic extended family and local residents about the wisdom of sacrificing and following the shari'ah of Prophet Ibrahim AS, fostering awareness and participation of the Aviation Polytechnic family and local residents in fostering a love for others in the manifestation of gratitude and piety Allah SWT; and 3) evidence-based learning, in which the